1976
DOI: 10.1037/0022-0663.68.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive styles, spatial ability, and school achievement.

Abstract: The present research was designed to study the interrelationships of intelligence, field independence, analytic cognitive style, and spatial and perceptual abilities among 201 boys, age 10-11 years. The contribution of cognitive style to the prediction of differences in attainment in English and mathematics was also investigated. Substantial overlap was confirmed between field independence and intelligence, but there were significant residual correlations (p < .01) between field independence and mathematics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 23 publications
3
37
0
Order By: Relevance
“…Since then numerous studies have reported a correlation between measures of FDI and various types of abilityspecificaly general intelligence and spatial aptitudes (Bloom-Feshbach, 1980;Laosa, 1980;McKenna, 1983McKenna, ,1984McKenna, Duncan, & Brown, 1986). However, some authors consider FDI to be entirely distinct from intelligence; their view is supported by the inconsistency of the relationship between the two variables, and by the numerous sources of variation which modify the relationship when it is present (Bush & De Ridder, 1971;Foms & Amador, 1990;Linn & Kyllonen, 1981;Satterly, 1976). Moreover, some authors invoke basic arguments which go beyond the empirical question of relationships beween measures.…”
mentioning
confidence: 89%
“…Since then numerous studies have reported a correlation between measures of FDI and various types of abilityspecificaly general intelligence and spatial aptitudes (Bloom-Feshbach, 1980;Laosa, 1980;McKenna, 1983McKenna, ,1984McKenna, Duncan, & Brown, 1986). However, some authors consider FDI to be entirely distinct from intelligence; their view is supported by the inconsistency of the relationship between the two variables, and by the numerous sources of variation which modify the relationship when it is present (Bush & De Ridder, 1971;Foms & Amador, 1990;Linn & Kyllonen, 1981;Satterly, 1976). Moreover, some authors invoke basic arguments which go beyond the empirical question of relationships beween measures.…”
mentioning
confidence: 89%
“…Among adolescents, significant relationships between measures of field dependence and overall academic performance are often reported (Erginel, 1972;Roberge and Flexer, 1981;Satterly, 1976Satterly, , 1979. These relationships can be inteipreted in terms of the overlap with standard ability measures (Erginel, 1972;Roberge and Flexer, 1981;Humphreys and Parsons, 1977).…”
Section: Educational and Vocational Interests And Achievementmentioning
confidence: 99%
“…Feij (1976) found that mathematics-trained students performed better than arttrained students on two embedded figures tests. There can be little doubt that there is a relationship between performance on a variety of embedded figures tests and mathematical ability (Dubois and Cohen, 1970;Ghuman, 1978;Roberge and Flexer, 1981;Satterly, 1976Satterly, , 1979Vaidya and Chansky, 1980). Once again the question remains whether this has anything to do with cognitive style.…”
Section: Educational and Vocational Interests And Achievementmentioning
confidence: 99%
“…Positive relations have been found between the field-independence and the performances in conservation tasks (Fleck, 1972;Dolecki, 1967;Finley, Sola and Cowan, 1977;Pascual-Leone, 1966Nodelman, 1965;Huteau and Rajchenbach, 1978;cited by Huteau, 1980) and in tasks relative to the space representation (La Crosse, 1966;Pascual-Leone, 1969;Satterly, 1976;cited by Huteau, 1980). However, no significant relation has been found between the subjects' cognitive style and the performances in multiplicative classification tasks and in class inclusion tasks (Pascual-Leone, 1969; Grippin, Ohnmacht and Clarck, 1973;Finley et al, 1977;cited by Huteau, 1980) on one hand, and the performances in seriation tasks (Huteau and Rajchenbach, 1978;Grippin et al, 1973;cited by Huteau, 1980) on the other hand.…”
Section: 51mentioning
confidence: 99%